A legitimidade democrática da construção dos precedentes judiciais : uma crítica ao incidente de resolução de demandas repetitivas - Lyra, Romulo Cruz Britto (2018)
This thesis aims to study the concept of legitimacy of political power based on the bases of the Democratic Rule of Law. It focuses on the theories of Luigi Ferrajoli, Jürgen Habermas and Hannah Arendt, whose foundations demand that legitimate power be derived from the valorization of intersubjectivity, communication between citizens and the necessary affirmation of human/fundamental rights, even if against majority. After these premises, we proceed to the reflection of the legitimacy of the exercise of jurisdiction, moment where we present the textualist, substancialist and proceduralist theories. The proceduralist theories, more adequate in the Democratic Rule of Law, had influenced the current Code of Civil Procedure, especially those developed by Fazzalari and Habermas. The principles of the effective contradictory and cooperation (or cooperative model of process) came from these two theorists and serve as an element of legitimation. Then, we discuss the creation, with CPC, of a system of precedents in Brazil, as a valuation of judicial decisions and an attempt to solve slowness of judicial activity. We investigate the singularities that surround the institute in a system that mixes a Roman- Germanic origin with typical common law mechanism. After this, we talk about the Incident of Resolution of Repetitive Claims (IRDR), a mechanism destined to form judicial precedents from the uniform solution of isomorphic demands. This institute is inspired by the German Law (Musterverfahren) and English Law (Group Litigation Order). However, some aspects of the IRDR are solipsistics, disconnected from the aforementioned valuation of intersubjectivity, here are them: the imposition of judicial precedent to absent litigants and the restriction to overrule the precedent. Based on the national doctrine, mainly, we verified the need to control the representation. In addition, the participation of all those initially legitimated to the overruling of the precedents is necessary, especially when we consider the idea of Habermasian self-legislator citizen. In the end, we concluded that every facet of political power must legitimize itself in every act always through presuppositions of communication between citizens and the valorization of human/fundamental rights